THE RELATIONSHIP BETWEEN BLOOD PRESSURE CONTROL AND THE DEGREE OF HYPERTENSION IN HYPERTENSIVE PATIENTS AT THE OUTPATIENT POLY OF BHAYANGKARA BRIMOB HOSPITAL KELAPADUA DEPOK IN 2023 - Ma’rifatun, Siti; Khamid, Abdul (HEARTY, 2025)
Background: Based on a preliminary study conducted at Bhayangkara Brimob Hospital Kelapadua Depok, it was found that as many as (90%) 18 out of 20 patients with hypertension claimed not to have made efforts to control blood pressure. Purpose: To determine the relationship between blood pressure control and the degree of hypertension in hypertensive patients at the outpatient poly of Bhayangkara Brimob Hospital Kelapadua Depok. Methods: Cross sectional through a point time approach where samples were taken using a total sampling of 50 respondents. Data analysis using chi square test. Results: Shows blood pressure control is associated with the degree of hypertension (p-value 0,007). Conclusion: There is a relationship between blood pressure control and the degree of hypertension. It is expected that the hospital can provide information and health education about efforts to control blood pressure during home treatment, so that blood pressure can be controlled properly and the impact of complications from hypertension can be avoided.